Passive remediation of metal and sulfate-rich acid mine drainage using a sulfate reducing bioreactor - Muhammad, Siti Nurjaliah (2016)
Acid mine drainage (AMD) is an environmental pollution that needs to be treated for sustainable environment in the future. Sulfate reducing bioreactor is one of the promising AMD treatments which can improve the health and conditions of mine water in an economical and sustainable way. The characterization of the treatment media used for AMD remediation was done for spent mushroom compost (SMC), limestone, and activated sludge. The SMC greatly assisted the removals of sulfate and metals and also acted as an essential carbon source for bacterial sulfate reduction (BSR). A column experiment was conducted to evaluate the performance of sulfate-reducing bioreactor in a continuous flow system in anoxic condition. The treatment media that composed of 40% crushed limestone, 30% SMC, 20% activated sludge and 10% woodchips were used in the column experiment. Generally, Fe, Pb, Cu, Zn, and Al were effectively removed in the treatment with 87 to 100% removals. However, Mn was not successfully removed from the treatment at the end of experiment despite initial Mn reduction during the early phase of the experiment. It was found from the column experiment that the first 15 days of treatment was an essential phase for the removal of most metals where contaminants were primarily removed by the BSR in reducing condition, in addition to calcite dissolution function. The treatment condition was favored by the availability of sufficient carbon source from the organic materials to enable bacterial sulfate reduction to occur effectively. The importance of bacterial sulfate reduction mechanism in the presence of organic materials was also supported by the metal accumulation analysis in the treatment substrates that primary metal accumulation occurs mainly through metal adsorption onto the organic matter and Fe/Mn oxides fractions.